2012
DOI: 10.1530/joe-12-0252
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miRNAs in ovarian follicular and luteal development

Abstract: Although much progress has been made in the genetic dissection of biological networks involved in follicular/luteal development in the mammalian ovary, the gene regulation mechanisms involved are still poorly understood. Over the last 10 years, miRNAs have emerged as master regulators of tissue growth and differentiation in animals. However, compared with other body tissues, little is still known about the functional involvement of miRNAs in the ovary. Several studies have identified miRNA populations specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
110
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 76 publications
3
110
0
1
Order By: Relevance
“…IL8 is the gene that encodes for interleukin 8, a chemokine and mediator of the inflammatory response, a chemo-attractant, and angiogenic factor [29]. IL8 is implicated in steroid synthesis in the late follicular and ovulatory follicle in both bovine [30] and humans [23].…”
Section: Discussionmentioning
confidence: 99%
“…IL8 is the gene that encodes for interleukin 8, a chemokine and mediator of the inflammatory response, a chemo-attractant, and angiogenic factor [29]. IL8 is implicated in steroid synthesis in the late follicular and ovulatory follicle in both bovine [30] and humans [23].…”
Section: Discussionmentioning
confidence: 99%
“…An involvement in the regulation of follicle function has been proposed for several miRNAs (reviewed in Donadeu et al (2012)), although most evidence to date derives from results using granulosa cell cultures. Moreover, physiological changes in the expression of miRNAs supporting putative roles during follicle development have often not been demonstrated , Yang et al 2012, Dai et al 2013, and detailed spatiotemporal miRNA profiles during development are not available.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is estimated that miRNAs may be responsible for regulating >70% of the coding genes in the human genome (11). Emerging data have demonstrated that the abnormal expression of miRNAs contributes to a number of diverse biological and pathological processes in cancer cells, including in cell proliferation, cell cycle, differentiation, development, apoptosis, migration, invasion and metastasis (12)(13)(14). Previous studies have revealed that miRNAs are involved in the carcinogenesis and progression of several types of human cancer as either oncogenes or tumor suppressors, depending on the functions of their target mRNAs (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%